Om språkbruk, generaliseringar och ett besvärligt material - Westum, Asbjørg (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
This article deals with narratives from northern Sweden about the Spanish flu pandemic (1918–1920). There are about 50 narratives collected between ca. 1950 and 1980. All of them were elicited in interviews: some were told in interaction with two or more informants, some are told by one informant in interaction with the interviewer, and some are monologues. There are different interviewers. The interviews have not been planned or conducted in a systematic and consistent way, or with a purpose to investigate the informants’ experiences of the Spanish flu. Rather, the main purpose seems to have been to elicit stories about “the old days”. Drawing on linguistic choices from the material as a whole, this article discusses the informants’ notion of the pandemic and their conceptions of etiology. The article concludes that the most conspicuous feature is what is not mentioned by any informant, namely the word influenza. Further, the Spanish flu clearly belongs to a past era that has no resemblance to modern society. It was an era characterized by suffering, poor sanitary conditions and starvation. As well, the article briefly discusses the critique of medical humanities and the study of illness narratives for the lack of systematic analyses and syntheses of how these are constructed in general.